At the Bench: Preclinical rationale for CTLA‐4 and PD‐1 blockade as cancer immunotherapy. Issue 1 (26th April 2013) - Intlekofer, Andrew M.; Thompson, Craig B.
Abstract : Basic Research Review for Clinicians: The cellular and molecular mechanisms of CTLA‐4 and PD‐1 function, and implications for tumor immunotherapy. Abstract : Tumors can avoid immune surveillance by stimulating immune inhibitory receptors that function to turn off established immune responses. By blocking the ability of tumors to stimulate inhibitory receptors on T cells, sustained, anti‐tumor immune responses can be generated in animals. Thus, therapeutic blockade of immune inhibitory checkpoints provides a potential method to boost anti‐tumor immunity. The CTLA‐4 and PD‐1Rs represent two T cell‐inhibitory receptors with independent mechanisms of action. Preclinical investigations revealed that CTLA‐4 enforces an activation threshold and attenuates proliferation of tumor‐specific T lymphocytes. In contrast, PD‐1 functions primarily as a stop signal that limits T cell effector function within a tumor. The unique mechanisms and sites of action of CTLA‐4 and PD‐1 suggest that although blockade of either has the potential to promote anti‐tumor immune responses, combined blockade of both might offer even more potent anti‐tumor activity. See related review At the Bedside: CTLA‐4 and PD‐1 blocking antibodies in cancer immunotherapy.